Arbuscula Mycorrhizal Fungi on The Rhizosphere Three in The Ex-Sand Mine at Cipancur-Kuningan West Java - Ika Karyaningsih; Redi; Nina Herlina; Desti Siti Alfiyah (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2024)
Sand and stone mining activities in Kuningan Regency cause damage to soil and environmental ecosystems, so reclamation and revegetation are carried out. The purpose of this study is to determine the existence of indigenous / local Arbuscular Mycorrhizal Fungi (FMA) found in the rhizozofer stands of Sengon (Paraserianthes falcataria) and Acacia (Acacia mangium) which are revegetation plants on the land of former sand and stone mines Cipancur village, Kalimanggis district, Kuningan regency. Sampling using the composite sampling method, FMA isolation technique using the wet pour method is then continued with the centrifugation technique and root colonization observation technique using the root staining technique (staining). The temperature of the ex-mining soil ranges from 28C – 29C, the soil pH is 5.5 including acidic, the soil moisture varies between wet, medium (slightly wet) and dry (dry) but during the rainy season the soil will become wet and even flooded. The results showed that there were 5 genera, it are Acaulospora, Glomus, Gigaspora, Sclerocytis and Scutellospora. The dominant genus is Glomus. The highest spore density was found in Sengon stands with 1,157 spores per 50 grams of soil. The highest percentage of AMF infection was at the root of Sengon stands at 69% from the ex-sand mining area.